2018
DOI: 10.1111/ijet.12138
|View full text |Cite
|
Sign up to set email alerts
|

On the advantages and disadvantages of being the first mover under rules of k names

Abstract: Rules of k names are methods that allow two potentially conflicting parties to share the power to appoint officers. One of the parties (the proposer) selects k candidates from a larger pool, and then the other party (the chooser) selects the winner from this restricted list. We investigate conditions under which the two parties could agree ex ante on the distributions of roles, one of them preferring to be the chooser and the other preferring to be the proposer. We show that this may not always be possible, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Another inequality parameter is the First Mover Advantage. While recommending Rule of k Names family, Barberà and Coelho (2018) suggested that SL mechanism migh have a heavier first mover advantage, but CRk and ASL can decrease it. Table 5.14 shows the payoff difference between the first and second mover.…”
Section: First Mover Advantagementioning
confidence: 99%
“…Another inequality parameter is the First Mover Advantage. While recommending Rule of k Names family, Barberà and Coelho (2018) suggested that SL mechanism migh have a heavier first mover advantage, but CRk and ASL can decrease it. Table 5.14 shows the payoff difference between the first and second mover.…”
Section: First Mover Advantagementioning
confidence: 99%
“…Both rules of appointment refer to important decision problems and belong to a family of procedures that we have called Rules of k Names in previous work (Barberà and Coelho, 2008, 2010, 2017) and Barberà and Coelho (2018). Given a kfalse{1,,boldcfalse}$k\in \lbrace 1,\ldots ,\mathbf {c }\rbrace$ exogenously fixed, one of the parties (the proposer) selects k$k$ candidates out of the c$\mathbf {c}$ available ones, and then the other party (the chooser) picks one winner out of that shortlist proposed by the opponent.…”
Section: Introductionmentioning
confidence: 99%
“…Both rules of appointment refer to important decision problems and belong to a family of procedures that we have called Rules of k Names in previous work (Barberà and Coelho, 2008, 2010, 2017 and Barberà and Coelho (2018). Given a k ∈ {1, .…”
Section: Introductionmentioning
confidence: 99%